Advances in the Study of the Potential Hepatotoxic Components and Mechanism of Polygonum multiflorum. (30th September 2020) - Yu, He-Shui; Wang, Lin-Lin; He, Ying; Han, Li-Feng; Ding, Hui; Song, Xin-Bo; Gao, Xiu-Mei; Yun, Nai-Ru; Li, Zheng
Abstract : The roots of Polygonum multiflorum (PM) (He Shou Wu in Chinese) are one of the most commonly used tonic traditional Chinese medicines (TCMs) in China. PM is traditionally valued for its antiaging, liver- and kidney-tonifying, and hair-blackening effects. However, an increasing number of hepatotoxicity cases induced by PM attract the attention of scholars worldwide. Thus far, the potential liver injury compounds and the mechanism are still uncertain. The aim of this review is to provide comprehensive information on the potential hepatotoxic components and mechanism of PM based on the scientific literature. Moreover, perspectives for future investigations of hepatotoxic components are discussed. This study will build a new foundation for further study on the hepatotoxic components and mechanism of PM.